T-786c Polymorphism in nitric oxide synthase 3 gene and Nitrit Oxide Level of Diabetic Retinopathy in Javanese Population - Welkriana, Putri Widelia; -, Sunarti; Hastuti, Pramudji (Indonesian Journal of Biotechnology, 2011)
AbstractComplication of retinopathy in type 2 DM is caused of lower level of NO. Nitric oxide level is synthesizedfrom L-arginin in reaction that catalyze Nitric oxide synthase (NOS) 3. The T-786C mutation in NOS 3 genedecreases the expression of nitric oxide synthase (NOS) 3 so decreases NO synthesis. To investigate theassociation between T-786C polymorphism in NOS 3 gene with NO level of diabetic retinopathy patients. Thisstudy was a case control study, consist of 40 patient of type 2 diabetic with DR (case group) and 40 patient oftype 2 diabetic without DR (control group) of Javanese ethnic. The genotyping of T-786C polymorphism wasperformed by PCR-RLFP. Level of NO was measured by spectrophotometry. Chi square test and odd ratiowere used to analyze the association of the T-786C polymorphism in NOS 3 gene with DR. Differences ofNO level between TT and TC genotypes were analyzed using independent t test. The distribution of T-786Cpolymorphism in NOS 3 gene of DR subjects showed that frequency of TT genotype was 22.5% and TC genotypewas 77.5%. Non DR subjects showed the frequency of TT genotype was 50% and TC genotype was 50%, (p=0.011). Frequency of T allele in DR group was 61.25% and C allele was 38.75%, and frequency of T allele in nonDR group was 75% and C allele was 25%, (p= 0.62). Odd ratio of TC genotype was 3.444(CI; 95% : 0.964-3.735)and C allele was 1.898 (CI; 95% : 1.310-9.058). The NO level of TC genotype was 1.43+0.126 and TT genotypewas 11.27+5.87 (p=0.000). Level of NO between RD and non RD showed not different significantly (p=0.160)for retinopathy. The T-786C polymorphism of NOS 3 gene is risk factor for retinopathy in type 2 DiabetesMellitus. Individual with TC genotype of NOS 3 gene has lower level of NO than TT genotype.Keywords : Diabetic Retinopathy, Polymorphism, Nitric Oxide, Nitric Oxide Synthase.